The role of obesity and gestational diabetes on placental size and fetal oxygenation. (1st January 2021) - Bianchi, Chiara; Taricco, Emanuela; Cardellicchio, Manuela; Mandò, Chiara; Massari, Maddalena; Savasi, Valeria; Cetin, Irene
Abstract: Introduction: Maternal pregestational obesity is a significant risk factor for adverse pregnancy outcomes, such as gestational diabetes. Both these conditions can have an impact on placental development and affect maternal-fetal exchanges, compromising fetal metabolic status. The aim of the study is to investigate the influence of pre-pregnancy BMI on placental size and to evaluate the role of obesity and gestational diabetes mellitus (GDM) on fetal oxygenation in overweight and obese pregnant women. Methods: 208 normal weight (NW), 57 overweight (OW) and 69 obese (OB) women were studied at elective cesarean section (CS) at term. 10 OW and 24 OB women were affected by GDM. Maternal, fetal and placental data were collected. Respiratory gases and acid-base balance were measured in umbilical venous and arterial blood. Results: Placental weight and thickness were higher in OB pregnancies. Lower fetal-placental ratios (F/P) were found in GDM pregnancies, both OW and OB. Fetuses from OB mothers were more hypoxic and acidemic compared to NW, particularly when complicated by GDM. Discussion: In agreement with previous studies, our data show that placentas from OB and GDM pregnancies are heavier and thicker, suggesting that an unbalanced pregestational nutritional status can decrease the placental efficiency in maternal-fetal exchanges. Fetuses from obese women are also hypoxic and acidemic, while fetuses from gestational diabetic mothers are hypoxic, reflecting that an altered pre-pregnancy BMI can affect fetal oxygenation, and GDM can play an additional detrimental role, thus worsening placental function and fetal oxygenation. Highlights: Obese women with gestational diabetes showed higher placental weight and thickness and lower fetal–placental weight ratio. Overweight patients with GDM had significantly lower umbilical arterial pO₂ and umbilical venous-arterial pO2 difference. Obese had lower values of pO2, O2  content, pH and lactate in umbilical artery and vein while O2  saturation only in vein.